UPAYA MENINGKATKAN HASIL BELAJAR IPA MATERI PEWARISAN SIFAT MELALUI MODEL COOPERATIVE LEARNING TIPE STUDENT TEAM ACHIEVEMENT DIVISION(STAD)SISWA KELAS 9H DI SMP NEGERI PAKUSARI JEMBER TAHUN PELAJARAN 2018/2019 - Endah Noer Aini (JURNAL PEMBELAJARAN FISIKA, 2020)
Abstract. Natural Science learning that took place 9H class at Pakusari State Junior High School in 2018/2019 still did not get the results desired, this is because the learning model used was not optimal to achieve student learning outcomes in accordance with the Curriculum Target. The formulation of the problem in this study are (1) How the Student Team Achievement Division (STAD) learning model can improve the learning outcomes of inheritance science material in 9H grade students of Pakusari State Junior High School in Jember 2018/2019 academic year. The data obtained in this study include the average evaluation learning outcomes for the first cycle that is 83.94, for the second cycle that is 85, the evaluation results can be seen that there is a significant increase in the average student learning outcomes from Cycle I to Cycle II, which is 1.05. This shows that in the first cycle students' learning completeness has not been achieved that is equal to 89.47%, while in the second cycle increased to 92.10% which suadah fulfill the minimum completeness of 75 and the average grade set is 85, the second cycle shows an increase of 1.05. Thus in the second cycle has reached the target, that learning the STAD Coopetive Learning type can improve the results of mathematics learning achievement. Keywords: STAD, IPA results